Kepemimpinan dan Kinerja Pimpinan Perempuan - Wirasandi Wirasandi; Hary Murcahyanto; Mawardi Mawardi; Abdul Majid Junaidi; Rasyid Ridho Hamidy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to, a) determine the performance of female village heads and village heads in carrying out their duties; b) to find out the perceptions of leaders, village staff, and the community of three villages and one sub-district in East Lombok Regency regarding the performance of female village heads and village heads; c) to find out the challenges and obstacles faced in carrying out their leadership. The method used is a qualitative method with a case study approach located in four locations in East Lombok Regency. Methods of data collection using observation, interviews, and documentation. Data analysis is data reduction, data presentation, and conclusion drawing. Test the validity of the data by deepening observations, in-depth interviews, and triangulation. The results of this study indicate that the performance of the female village head is good, responsible discipline, and never procrastinated on her duties. And the distribution of development is continuously carried out by the programs that have been implemented. This was acknowledged by village staff and communities in three villages in East Lombok Regency. The community's perception of the performance of the female village head/lurah is that the performance of the female village head/lurah is quite good when compared to the performance of the male village head/lurah. Female village heads have high participation, often provide examples, and invite the community to work together and make the village they lead more advanced. The challenges and obstacles faced by female village heads are when taking care of their household. In conclusion, the performance of female village heads in East Lombok Regency is considered to be good, responsible, and disciplined. Public perception is quite good. The challenge in addition to being a leader in her village is also being a housewife who has to be able to divide her time between household work and her official work. Keywords: Leadership, Performance, Women